Indicator Organisms: What Every Floridian May Want to Know about Microbiological Water Quality - Max Teplitski; J. Dwain Butler (EDIS)
SL-259, a 3-page fact sheet by Max Teplitski and J. Dwain Butler, is designed to help the reader interpret the results of a microbiological water test. Includes references. Published by the UF Department of Soil and Water Sciences, March 2008.